Collaborative writing in the EFL classroom: The effects of L1 and L2 use. (August 2018) - Zhang, Meixiu
Abstract: Previous research has demonstrated that collaborative writing (CW) tasks are useful instructional activities as they increase the learning opportunities in language classrooms (Li & Zhu, 2017). However, when implementing CW tasks, language teachers in contexts where learners share an L1 are faced with a question—should learners interact with peers in the L1 or the L2? Existing research has focused on analyzing the functions of L1 interaction in CW, but no research has examined the effects of L1 use on the co-constructed texts. The present study addressed this question by investigating the effects of L1 and L2 use on the complexity, accuracy, fluency, and text quality of learners' co-constructed texts. Thirty-five pairs of intermediate EFL learners were placed in two groups to write argumentative essays in English. First, group 1 ( n  = 18 pairs) interacted in the L1 and group 2 ( n  = 17 pairs) interacted in the L2. Next, the groups switched the language for interaction and wrote a second essay. The co-constructed essays were rated for complexity, accuracy, fluency, and text quality. The results indicate that collaboration in the L1 leads to higher syntactic complexity but no differences in accuracy, fluency, and text quality. Theoretical and pedagogical implications were discussed.